Visual Search and Visual Discomfort. (January 2013) - O'Hare, Louise; Clarke, Alasdair D; Hibbard, Paul B
Certain visual stimuli evoke perceptions of discomfort in non-clinical populations. We investigated the impact of stimuli previously judged as uncomfortable by non-clinical populations on a visual search task. One stimulus that has been shown to affect discomfort judgments is noise that has been filtered to have particular statistical properties (Juricevic et al, 2010 Perception 39 884–899). A second type of stimulus associated with visual discomfort is striped patterns (Wilkins et al, 1984 Brain 107 989–1017). These stimuli were used as backgrounds in a visual search task, to determine their influence on search performance. Results showed that, while striped backgrounds did have an impact on visual search performance, this depended on the similarity between the target and background in orientation and spatial frequency. We found no evidence for a more generalised effect of discomfort on performance.